Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1051/aas:2000103
|View full text |Cite
|
Sign up to set email alerts
|

Dust outflows from quiescent spiral disks

Abstract: Abstract.We have conducted a search for "dust chimneys" in a sample of 10 highly-inclined spiral galaxies (i = 86 − 90• ) which we had previously observed in the Hα emission line (Rand 1996). We have procured B-band CCD images for this purpose and employed unsharp-masking techniques to accentuate the structure of the dust lane. A scattering+absorption radiation transfer model enabled us to separate 5 galaxies from the sample which are sufficiently inclined (i > 87• ) for us to reliably identify and quantify du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 61 publications
(87 reference statements)
3
55
3
Order By: Relevance
“…• 01 (Bianchi 2007), the galaxy is displaying a dust lane, visible along the entire disc and with an extensive vertical dust distribution (Howk & Savage 1999;Thompson et al 2004), although we note that Alton et al (2000a) consider this galaxy to be too highly inclined to make any unambiguous claims about extraplanar dust. A global fit of extinction by the dust distribution to optical images was carried out in Bianchi (2007), giving a dust scalelength of 70 or 6.7 kpc, which is 75% larger than the stellar disc scalelength.…”
Section: Ngc 4217mentioning
confidence: 88%
See 1 more Smart Citation
“…• 01 (Bianchi 2007), the galaxy is displaying a dust lane, visible along the entire disc and with an extensive vertical dust distribution (Howk & Savage 1999;Thompson et al 2004), although we note that Alton et al (2000a) consider this galaxy to be too highly inclined to make any unambiguous claims about extraplanar dust. A global fit of extinction by the dust distribution to optical images was carried out in Bianchi (2007), giving a dust scalelength of 70 or 6.7 kpc, which is 75% larger than the stellar disc scalelength.…”
Section: Ngc 4217mentioning
confidence: 88%
“…The dust lane extends from the centre out to the edges along the major axis, and although Howk & Savage (1999) state that the galaxy has no detectable vertically extended dust or ionised gas, Alton et al (2000a) claim this galaxy to be insufficiently edge-on to make any definite statements about extraplanar dust. The dust distribution has been previously modelled using global fits to the dust lane extinction in optical images (Xilouris et al 1999), leading to a dust scalelength of 100 or 7.8 kpc, which is about 10% larger than the corresponding stellar disc scalelength.…”
Section: Ngc 5907mentioning
confidence: 96%
“…To evaluate the latter uncertainty we fitted a modified black body from 100 to 200 µm assuming an β = 1.5. Grain emissivities larger than 2 or smaller than 1.5 have not been observed at these wavelengths in average interstellar medium conditions of normal galaxies (see Alton et al 2000 and references therein). The temperatures obtained are ∼ 15% smaller than the values given in Table 5.…”
Section: The Spectral Energy Distributionsmentioning
confidence: 99%
“…Using SCUBA sub-millimeter observations of the nearby normal galaxy NGC 891 Israel et al (1999) found a cold dust component at a temperature ∼ 21 K. For the same galaxy Alton et al (2000) found that, though the bulk of the sub-millimeter emission is associated with the molecular gas, it extends beyond the optical radius, where it follows the distribution of the neutral HI gas. This dust component could be easily removed during the ram pressure stripping process occurring on cluster galaxies.…”
Section: Introductionmentioning
confidence: 98%
“…These galaxies are closer to edge-on, meaning that some of the dust in the line of sight may be far from the nucleus. As the scale heights of dust in spiral galaxies tend to be small (Alton et al 2000), though, these spectra are likely to still contain a substantial contribution from nuclear dust. This suggests that the hydrocarbons in the dust in these galaxies are robust enough to survive unchanged in quite harsh conditions.…”
Section: Dust Production and Surv Viv Val In Galaxiesmentioning
confidence: 99%